Targeting energy, nucleotide, and DNA synthesis in cancer - Vider, Ben Zion (Frontiers in Oncology, 2025)
Cancer represents a disease in which genetic alterations reassert the dominance of the cell cycle over all other cellular processes. From the earliest stages of evolution, the coupling of energy utilization with nucleotide and DNA synthesis established replication as the central driver of cellular behavior. In cancer, this evolutionary logic is replayed in reverse. Hyperactivation of the cell cycle drives hyperactivation of its metabolic core, while the loss or inactivation of tumor suppressor genes, many of which are cell-type specific, links this accelerated proliferation with altered cell fate. With virtually unlimited energy available, malignant cells amplify nucleotide production and DNA replication without restraint. This Perspective proposes that anti-metabolites, long-standing pillars of cancer therapy, can be redesigned to target the main components of DNA metabolism. By rationally combining these anti-metabolites into synergistic triads (three anti-metabolites, well selected, administered together), therapy may dismantle the metabolic foundations of cancer and achieve more durable control across tumor types. The combinations that could yield meaningful progress are outlined and discussed.